Improving the chronological framework for Laugerie-Haute Ouest (Dordogne, France). (February 2019) - Verpoorte, Alexander; Cosgrove, Richard; Wood, Rachel; Petchey, Fiona; Lenoble, Arnaud; Chadelle, Jean-Pierre; Smith, Colin; Kamermans, Hans; Roebroeks, Wil
Abstract: Laugerie-Haute is one of the key sequences of the European Upper Paleolithic. However, the absolute chronology of the sequence is not well-established, and recently the integrity of the layers has been called into question. In this paper, we present new radiocarbon dating results for the entire sedimentary sequence at Laugerie-Haute Ouest, which contains important "Aurignacian V" and Solutrean assemblages. Our results show that the entire Laugerie-Haute Ouest sequence was deposited in a period of 8500–10, 000 years, dating between 28 and 19 cal. kBP. Highlights: We present an improved chronology of the Laugerie-Haute Ouest sequence. The radiocarbon chronology suggests stratigraphic integrity of the Solutrean levels. The results support the existing chronological framework for the Upper Paleolithic of Southwest France. The dates suggest that only the early part of the Aurignacian V or Proto-Solutrean is represented in southwestern France.